PENGARUH BRAND IMAGE DAN KUALITAS PRODUK TERHADAP MINAT MASYARAKAT MENABUNG DI BSI KCP PETTARANI MAKASSAR - Trimulato; Wahyu, Febriyani; Efendi, Ahmad (Universitas Ratu Samban, 2023)
The purpose of this study was to determine the effect between brand image and product quality in increasing people's interest in saving. This study uses quantitative research with a causal associative approach, which aims to determine how the relationship between two or more variables. Sources of data in this study consisted of primary data and secondary data, while the data collection technique used in this study was a questionnaire method distributed via social media. The results of this study are that there is a positive influence between brand image and product quality in increasing people's interest in saving at Indonesian Islamic banks. With a coefficient value of brand image on the intention to save as much as 0.393 and a coefficient value of product quality on the intention to save as much as 0.497. Bank Syariah Indonesia, which is a new bank resulting from the merger of three Islamic banks, must build a positive brand image and must also have good and quality products.